Regulation and Technology Innovation: A comparison of Stated and Formal Regulatory Barriers throughout the Technology Innovation Process - Engberg, Robert; Altmann, Peter (Journal of Technology Management & Innovation, 2015)
Regulation is often mentioned as a barrier to technology innovation in various industries. Delayed market entry, added resource requirements, stifled creativity, and added activities are some frequently mentioned complaints. The study presented here explored various claims of regulation acting as a barrier to technology innovation. Our findings indicate that formal statutory requirements only partly explain why regulation is perceived as a technology innovation barrier. Furthermore, our findings indicate several discrepancies between stated and formal regulatory barriers, and suggest that the majority of the stated barriers emerge within the organization during operationalization and the technology innovation process.